A rare case of acute psychosis as an isolated manifestation of extrapontine myelinolysis - Wan Sulaiman, Wan Aliaa; Fan , Kee Hoo; Basri, Hamidon; Hasan, Shariful; Mohd Sazlly Lim, Sazlyna; Yoke , Loong Foo; Siew , Mooi Ching; Ramachandran, Vasudevan; Mohamed, Mohd Hazmi; Hashim, Hasnur Zaman (SCIENCEDOMAIN international, 2014)
Aims and Background: Central pontine myelinolysis (CPM) and extrapontine myelinolysis (EPM) are recognized as osmotic demyelination syndrome (ODS. ODS is pathologically characterized by non-inflammatory demyelination of several brain structures with sparing of axons. This condition is usually associated with overzealous correction of hyponatraemia. Acute psychosis as the sole clinical manifestation is extremely rare. Presentation of Case: Hence, we report an interesting case of a middle-aged man who was diagnosed with EPM, following rapid correction of hyponatraemia and subsequently developed acute psychosis. He made a good recovery with supportive treatment alone. Discussion and Conclusion: The possibility of psychosis as a manifestation of ODS, particularly in patients with recent correction of hyponatraemia. The rate of correction of plasma sodium level is the key point for preventing ODS and its complications.